Optimal fiscal policy in a~model~with efficiency wages: the~case of Bulgaria - Aleksandar Vasilev (International Journal of Social Economics, 2022)
Purpose: This paper aims to explore the effects of fiscal policy in an economy with efficiency wages, consumption taxes and a common income tax rate. Design/methodology/approach: A dynamic general-equilibrium model with the government sector is calibrated to Bulgarian data (1999–2018). Two regimes are compared and contrasted – the exogenous (observed) vs optimal policy (Ramsey) case. Findings: The main findings are as follows: (1) The optimal steady-state income tax rate is zero. (2) The benevolent Ramsey planner provides three times lower amount of the utility-enhancing public services. (3) The optimal steady-state consumption tax needed to finance the optimal level of government spending is 18.7%. Originality/value: The focus of the paper is on the relative importance of consumption vs income taxation, as well as on the provision of utility-enhancing public services. Bulgarian economy was chosen as a case study due to its major dependence on consumption taxation as a source of tax revenue. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-08-2021-0488 .
Keywords: E32; 330; Ramsey policies; Efficiency wages; Unemployment; Bulgaria